The metabolic stress response to burn trauma: current understanding and therapies. Issue 10052 (1st October 2016) - Porter, Craig; Tompkins, Ronald G; Finnerty, Celeste C; Sidossis, Labros S; Suman, Oscar E; Herndon, David N
Summary: Major burns provoke a profound stress response, which is unrivalled in terms of its magnitude and duration. Evidence suggests that the pathophysiological stress response to severe burn trauma persists for several years after injury. Thus, there is a pressing need for novel strategies that mitigate this response and restore normal metabolic function in patients with burns. This is the first in a Series of three papers about the care of people with burns. In this paper, we review the current knowledge of the stress response to burn trauma, with a focus on hypermetabolism, muscle wasting, and stress-induced diabetes. We highlight recent developments and important knowledge gaps that need to be pursued to develop novel therapeutic strategies to improve outcomes in burn survivors.